2021
DOI: 10.1002/marc.202100035
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Routes to Single Chain Polymer Nanoparticles (SCNPs): Current Status and Perspectives

Abstract: Recent advances in polymer science make it possible to create single chain polymer nanoparticles (SCNPs), which can mimic the folding of natural macromolecules, such as protein and nucleic acid, in terms of their native and functional state. Even though considerable progress has been done during the last years, the synthesis of relatively controlled SCNPs with a good folding accuracy is still challenging due to lack of appropriate chemical synthesis techniques. Different types of SCNPs are developed with enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 89 publications
1
36
0
1
Order By: Relevance
“…Single-chain polymer nanoparticles (SCNPs) are a class of materials, developed mainly in the last two decades, supplying exceptionally small nanoparticles in the sub-20 nm range. This is accomplished thanks to their capability of self-folding by intramolecular interactions within a single polymer chain rather than forming multi-chain nanoobjects by intermolecular interactions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Single-chain polymer nanoparticles (SCNPs) are a class of materials, developed mainly in the last two decades, supplying exceptionally small nanoparticles in the sub-20 nm range. This is accomplished thanks to their capability of self-folding by intramolecular interactions within a single polymer chain rather than forming multi-chain nanoobjects by intermolecular interactions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Broad task‐specific applications are envisaged from biological engineering, catalysis, to interfacial manipulation [7–13] . In terms of connection mode, three strategies can be used including covalent bonding, dynamic covalent bonding and non‐covalent interactions to construct the SCNPs [14, 15] . Traditionally, the synthesis of SCNPS should be performed at an ultra‐low concentration of polymers (<0.1 mg mL −1 ) in order to avoid intermolecular crosslinking of the entangled chains [16] .…”
Section: Figurementioning
confidence: 99%
“…, tadpole and dumbbell) contain at least one intrachain folding block formed by a one-step, stepwise or orthogonal folding process. 55–63 To our surprise, more complex intracyclic folding nanoparticles have been scarcely reported. Rubio-Cervilla et al have reported the synthesis of single-ring nanoparticles mimicking natural cyclotides by a stepwise folding–activation–collapse process, in which a random copolymer is designed and adopted for two consecutive single-chain foldings via a photoactivated hetero Diels–Alder ring-closing reaction and copper( i )-catalyzed azide–alkyne cycloaddition reaction.…”
Section: Introductionmentioning
confidence: 98%
“…[39][40][41][42][43][44] Inspired by this intriguing biological phenomenon, a wide range of synthetic polymers have been rationally designed and subjected to intramolecular cross-linking to fold into defined architectures, in which macrocycle-bearing self-folding poly-mers primarily include monocyclic, bicyclic, and multicyclic polymers and their derivatives, [45][46][47][48][49][50][51][52][53][54] and single-chain nanoparticles with tunable sizes and shapes (i.e., tadpole and dumbbell) contain at least one intrachain folding block formed by a one-step, stepwise or orthogonal folding process. [55][56][57][58][59][60][61][62][63] To our surprise, more complex intracyclic folding nanoparticles have been scarcely reported. Rubio-Cervilla et al have reported the synthesis of single-ring nanoparticles mimicking natural cyclotides by a stepwise folding-activationcollapse process, in which a random copolymer is designed and adopted for two consecutive single-chain foldings via a photoactivated hetero Diels-Alder ring-closing reaction and copper(I)-catalyzed azide-alkyne cycloaddition reaction.…”
Section: Introductionmentioning
confidence: 99%